The Types and Levels of Code Mixing Based on Deddy Corbuzier Podcast Video on Youtube Channel - Mahardika, Yovinda; Fitrawati, Fitrawati (Universitas Negeri Padang, 2024)
This research investigated the types and levels of code mixing based on Deddy's podcast video on his YouTube channel. The aim of this research is to determine the types and the levels of code mixing in Deddy Corbuzier’s podcast. Qualitative the video, transcribing the video’s audio, identifying the code-mixing and level code- mixing, and re-checking. After the process, the result indicated that the most code-mixing used in the utterances of the guest star in Deedy's Corbuzier podcast video is intra-sentential with the total number is 108 method used in this study to analyze the data and describe the findings. There were 3 Podcast videos of Deddy Corbuzier anakyzed in this study: Agnez Mo.. Mantanku Ter…, Papa Meninggal, Azka Ikut Papa.. I Love You More Than You Know, 500 Juta Tuk Luna Maya.. Tapi.. Ada Tapinya..!!. Some methods followed to collect the data include searching the video, selecting and downloading the video, watching occurances, meanwhile followed by intra-lexical type is 7 occurances. Furthermore, the level of code mixing that mostly appears is clause type 50 occurances then followed by word level 36 occurances, phrase level 31 occurances, baster level 7 occurances, and idiom 1 occurances.